2010
DOI: 10.1007/s00422-010-0386-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of directional strengths in jointly stationary linear multivariate processes

Abstract: Identification and analysis of directed influences in multivariate systems is an important problem in many scientific areas. Recent studies in neuroscience have provided measures to determine the network structure of the process and to quantify the total effect in terms of energy transfer. These measures are based on joint stationary representations of a multivariate process using vector auto-regressive (VAR) models. A few important issues remain unaddressed though. The primary outcomes of this study are (i) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 19 publications
0
46
0
Order By: Relevance
“…This approach, devised specifically for the study of cardiac and respiratory oscillators, showed how cardiorespiratory interactions evolve with the process of aging [8]. In the frequency domain, the vector autoregressive parametrization of multivariate processes leads to formalize a spectral decomposition evidencing directed transfers of power [46], with each decomposition term describing a specific transfer function that includes direct effects, indirect effects, and interference effects [54]. Interestingly, all these approaches to the decomposition of multivariate interactions evidence the difficulty of providing a thorough separation of the causal sources of statistical dependence for the observed dynamics: the phase and frequency domain approaches make use of decomposition terms that account for the combined effects of different causal sources, while our information dynamics approach shows that the causal connections may serve simultaneously both components of the predictive information (i.e., information storage and information transfer, or cross information and internal information).…”
Section: Discussionmentioning
confidence: 99%
“…This approach, devised specifically for the study of cardiac and respiratory oscillators, showed how cardiorespiratory interactions evolve with the process of aging [8]. In the frequency domain, the vector autoregressive parametrization of multivariate processes leads to formalize a spectral decomposition evidencing directed transfers of power [46], with each decomposition term describing a specific transfer function that includes direct effects, indirect effects, and interference effects [54]. Interestingly, all these approaches to the decomposition of multivariate interactions evidence the difficulty of providing a thorough separation of the causal sources of statistical dependence for the observed dynamics: the phase and frequency domain approaches make use of decomposition terms that account for the combined effects of different causal sources, while our information dynamics approach shows that the causal connections may serve simultaneously both components of the predictive information (i.e., information storage and information transfer, or cross information and internal information).…”
Section: Discussionmentioning
confidence: 99%
“…In order to isolate the root cause, the DTF was utilized since it can be seen as the 'amount' of variation originated from each 'cause' variable to the 'effect' variable through direct and indirect paths (Gigi and Tangirala, 2010). Under this logic, the variable which 'contributed' the most to the variation in the process can be seen as the root cause of a disturbance.…”
Section: Results Of the Frequency Analysismentioning
confidence: 99%
“…For example, if causal relations exist from A to B and from B to C, there may be strong causality between A and C that can be confirmed by reachability, yet it is actually redundant. The study to identify whether the path is direct or indirect is underway in the temporal as well as the spectral domain (Gigi and Tangirala, 2010). Although it is possible, it is not efficient without looking at process knowledge.…”
Section: Using Process Knowledge To Validate Data-based Relationsmentioning
confidence: 99%